2020
DOI: 10.4236/as.2020.1112074
|View full text |Cite
|
Sign up to set email alerts
|

Biochar on Soil Chemical Properties and Beak Pepper (<i>Capsicun chinense</i>) Production

Abstract: The transformation and recycling of poultry litter through the pyrolysis process produces a co-product called biochar which, applied to the soil, improves the chemical characteristics of the soil and is used as a soil fertilizer due to its high content of nutrients to plants. The objective of this study was to assess the effect of biochar, produced from poultry litter wastes on soil chemical properties and the culture of the beak pepper (Capsicun chinense

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The exchangeable cation (magnesium, sodium and potassium) content increased linearly and quadratically with the concentrations of poultry litter biochar, agreeing with previous studies (I. C. B. D. Silva, et al, 2017;Tito et al, 2020). Figures 1E, 1F and 1G show that the magnesium, sodium and potassium concentrations (11.19, 1.61 and 4.40 cmolc kg -1 ) corresponded to the highest biochar rate (20 t ha -1 ); therefore, these values increased by approximately 26, 160 and 1.492%, respectively, compared with the control.…”
Section: Availablesupporting
confidence: 92%
See 2 more Smart Citations
“…The exchangeable cation (magnesium, sodium and potassium) content increased linearly and quadratically with the concentrations of poultry litter biochar, agreeing with previous studies (I. C. B. D. Silva, et al, 2017;Tito et al, 2020). Figures 1E, 1F and 1G show that the magnesium, sodium and potassium concentrations (11.19, 1.61 and 4.40 cmolc kg -1 ) corresponded to the highest biochar rate (20 t ha -1 ); therefore, these values increased by approximately 26, 160 and 1.492%, respectively, compared with the control.…”
Section: Availablesupporting
confidence: 92%
“…phosphorus increased with biochar, with the highest concentration (312.68 mg dm -3 ) occurring at the rate of 13.26 t ha -1 (Figure 1D). This represents a 3905% increase compared with the control, corroborating Tito et al (2020), who observed a 5131% increase in the P content. This significant increase is probably due to the direct supply of this element, which acted as a source of P, since potassium phosphate is part of the composition of biochar (Chaves et al, 2020); and to the reduced adsorption of P on the surface of mineral and organic colloids that was negatively charged due to the increase in pH (Cui, Wang, Fu, & Ci, 2011;Zhai et al, 2015).…”
Section: Availablesupporting
confidence: 87%
See 1 more Smart Citation
“…Some studies indicate that biochar could have detrimental effects, as there is a possibility that it alters nutrient availability or modifies soil structure growth [22]. On the other hand, other researchers highlight its benefits in correcting the chemical properties of the soil, although they remarked that their results in terms of plant growth are not very promising [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already been conducted with other crops using poultry litter biochar. For instance, Coomer (2013) achieved better results of cotton growth using 3 t ha -1 ; for 'biquinho' pepper (Capsicun chinense), 5 t ha -1 of biochar were recommended (TITO et al, 2020); doses from 100 to 150 g/plant were more adequate for the number of leaves, root length, fresh and dry biomass of leaves and roots of radish plants (Raphanus sativus L.) (CAVALCANTE et al, 2021); in the production and quality of melon (Cucumis melo L.) seedlings, 12 t ha -1 was considered the ideal dose for the development of these seedlings (LAURENTINO et al, 2021); similarly, 19 m 3 ha -1 of poultry litter biochar during 45 days after sowing were recommended for the growth of bell pepper (Capsicum annuum L.) (LIMA et al, 2019). As for corn crop, Inal et al (2015) applied 0, 2.5, 5, 10 and 20 g kg -1 of biochar and observed that plant growth and leaf concentrations of N, P, K, Zn, Cu and Mn increased according to the doses, revealing that this biochar can be effectively used as a source of these nutrients.…”
Section: Introductionmentioning
confidence: 99%